Implementation of Smart Helmets to Enhance Safety in Construction Projects in Malaysia - Abdul Aziz, Nur Ilham; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2026)
The construction industry remains one of the most risk sectors due to challenging site factors, heavy machinery operations, and insufficient real-time safety monitoring, all of contributing to an increased risk of workplace accidents. Conventional safety helmets provide only basic protection and are ineffective in detecting risks or monitoring workers' physical condition, mandating the use of more modern safety technology. This highlights the important role of adopting advanced technologies, such as smart helmets which is not only help monitor and manage potential hazards but also effectively reduce the risk of accidents, thereby improving overall safety and efficiency in construction project management. Thus, this paper discusses on the advantages of using smart helmet in construction projects in Malaysia, investigate the challenges that hinder the adoption of smart helmet in construction projects and suggest enhancement for the implementation of smart helmets in construction projects in Malaysia. The respondents involved in the interviews were construction professionals in Malaysia who have experience using smart helmets in construction project. The findings show that smart helmets improve worker safety through real-time monitoring, early hazard alerts, and systematic safety data collect, enabling for quicker and better inform decision-making. However, several barriers were observed, including workers limited digital literacy, technological limitations managing data issues, language problems during training, and inconsistent usage on-site. In order to resolve these issues, it is essential to provide continuous training, clear standard operating procedures, enhanced system reliability, and strong organizational support. In general, smart helmets have the potential to significantly improve safety performance in construction projects when implementation issues are successfully solved.